Subsurface Fluid Pressure and Rock Deformation Monitoring Using Seismic Velocity Observations. Issue 19 (11th October 2018) - Doetsch, Joseph; Gischig, Valentin S.; Villiger, Linus; Krietsch, Hannes; Nejati, Morteza; Amann, Florian; Jalali, Mohammadreza; Madonna, Claudio; Maurer, Hansruedi; Wiemer, Stefan; Driesner, Thomas; Giardini, Domenico
Abstract: Fluid pressure within the Earth's crust is a key driver for triggering natural and human‐induced seismicity. Measuring fluid pressure evolution would be highly beneficial for understanding the underlying driving mechanisms and supporting seismic hazard assessment. Here we show that seismic velocities monitored on the 20‐m scale respond directly to changes in fluid pressure. Our data show that volumetric strain resulting from effective stress changes is sensed by seismic velocity, while shear dislocation is not. We are able to calibrate seismic velocity evolution against fluid pressure and strain with in situ measurements during a decameter‐scale fluid injection experiment in crystalline rock. Thus, our 4‐D seismic tomograms enable tracking of fluid pressure and strain evolution. Our findings demonstrate a strong potential toward monitoring transient fluid pressure variations and stress changes for well‐instrumented field sites and could be extended to monitoring hydraulic stimulations in deep reservoirs. Plain Language Summary: The pressure of fluids in the subsurface is generally a function of depth as well as the regional geological history. Changes to the subsurface fluid pressure—be it natural or human induced—disturb the stress field and are known to drive volcanic eruptions, as well as to trigger earthquakes. For example, pressure increase by fluid injection for hydraulic stimulation and wastewater disposal has been linked to earthquake activity. Unfortunately, pressure measurements need direct access through boreholes, so that pressure data are only available for few locations. A method for estimating the spatial distribution of fluid pressure remotely would thus be highly beneficial. From measurements in a 20‐m‐scale experiment in granite, we find that fluid pressure propagation can be predicted from observed seismic velocity variations, based on a strong correlation between observed changes in seismic velocities and fluid pressure measured within the rock. As seismic velocities can be readily measured on the reservoir scale, our results demonstrate a strong potential of seismic velocity monitoring for remotely estimating fluid pressure changes in deep reservoirs, along faults, or in volcanic systems. The estimated pressure and stress changes could be an important input to real‐time risk analysis of fault reactivation and volcanic eruptions. Key Points: Seismic velocities measured in 20‐m‐scale in situ experiment respond directly to high‐pressure fluid injections In situ measurements of fluid pressure allow validation of seismic velocity measurements as proxy for field‐scale pressure monitoring Three‐dimensional time‐lapse seismic velocity tomography allows monitoring of fluid pressure propagation through its relationship to effective stress